Association between Dog Guardianship and HIV Clinical Outcomes. (July 2014) - Saberi, Parya; Neilands, Torsten B.; Johnson, Mallory O.
Despite numerous potential health outcomes of dog guardianship, their value has not been examined in the HIV-positive population. The study objective was to examine the relationship between dog guardianship and HIV clinical outcomes (antiretroviral adherence [≥95% versus <95%], HIV viral load [≥48 versus <48 copies/mL], and CD4 count) among HIV-positive individuals. The authors conducted a secondary analysis of baseline data of 370 HIV-positive men on antiretroviral regimen enrolled in the Duo Project. Generalized estimating equations were used for inferential regression analyses, while controlling for the focal dog guardianship variable and nonfocal covariates. Current dog guardianship was reported in 28.7% of participants. Dog guardianship may be associated with higher CD4 (coefficient = 60.6, P = .052) and adherence ≥95% (odds ratio [OR] = 1.80, P = .048); however, having a detectable viral load was not related to dog guardianship (OR = 0.94, P = .85). Further clinical research with detailed dog guardianship data is needed to further examine the association between dog guardianship and HIV clinical outcomes.